PENERAPAN MEDIA GAMBAR BERSERI UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SISWA KELAS III SD NEGERI 94 BEBA - Nurhilda; Nur Isnain Ali; Iskandar; Erni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the writing skills of essays in third-grade students of SD Negeri 94 Beba through the application of picture series media. Indonesian language learning emphasizes the development of reading and writing skills as essential prerequisites in various fields of study. Through classroom action research conducted in two cycles, it was found that students' writing skills before the media application were still low with a completion rate of 46.43%. After using picture series media, there was a significant increase in cycle I to 71.42% and cycle II to 78.57%. Picture series media is effective in helping students sequence ideas, develop stories, and improve grammar and punctuation. The results of the study indicate that the use of picture series media can significantly increase students' motivation, creativity, and writing competence. Therefore, this media is recommended as an effective learning innovation to improve simple essay writing skills in elementary schools.